Sleep Assessment During Shift Work in Korean Firefighters: A Cross-Sectional Study - Kyoung Sook Jeong; Yeon-Soon Ahn; Tae-Won Jang; Gayoung Lim; Hyung Doo Kim; Seung-Woo Cho; Chang-Sun Sim (Elsevier, 2019)
Background: This cross-sectional study assessed the sleep quality using the ActiGraph and investigated the relationship between the parameters of sleep assessment and the type of shift work in Korean firefighters. Methods: The participants were 359 firefighters: 65 day workers (control group) and 294 shift workers (shift work group: 77 firefighters with 3-day shift, 72 firefighters with 6-day shift, 65 firefighters with 9-day shift, and 80 firefighters with 21-day shift). Sleep assessments were performed using the ActiGraph (wGT3X-BT) for 24 hours during day shift (control and shift work group) and night shift and rest day (shift work group). The participants recorded bed time and sleep hours during the measurement period. Results: Sleep efficiency, total sleep time, and percentage of wake after sleep onset during night work were lower in the shift work group than control group (p < 0.05). Sleep efficiency decreased in night shift and increased in rest day, whereas wake after sleep onset increased in night shift and decreased in rest day (p < 0.05). Among shift work groups, sleep efficiency of 6-day shift was higher in day shift, and sleep efficiency of 21-day shift was lower in night shift than other shift groups (p < 0.05). Conclusion: We found that the sleep quality in night shift of the shift work group was poorer than the control group. As to the type of shift work, sleep quality was good in 6-day shift and poor in 21-day shift. Thus, fast rotating shift such as 6-day shift may be recommended to improve the sleep quality of the firefighters. Keywords: Firefighters, Shift work, Sleep, Sleep assessment